A possible advantage for the ’Polish’ morph of the Mute Swan - Bacon, P J (Wildfowl, 1980)
A hypothesis is advanced as to the possible advantage to the white phase ’Polish’ morph in Mute Swans Cygnus olor. The benefit is to the heterogametic female enabling her to breed early in low density populations. Its presence as a recessive condition in males may prevent its extinction in high density populations.